Порушення прав сільського населення при збиранні податків та оскарження дій фінагентів (середина 40-х – середина 50-х рр. ХХ ст.) - Гаврилов, В. (Сiверянський лiтопис, 2016)
Стаття присвячена вивченню проблеми збору фінансових та натуральних податків у перше післяокупаційне десятиріччя в сільській місцевості, аналізу порушень
прав населення при цьому, а також їхніх спроб протестувати та оскаржувати дії уповноважених осіб. Статья посвящена изучению проблемы сбора финансовых и натуральных налогов
в первое послеокупационное десятилетие в сельской местности, анализу нарушений
прав населения при этом, а также их попыток протестовать и обжаловать действия
уполномоченных лиц. This article is devoted to the problem of collecting financial and natural taxes in rural areas
in the first decade after the occupation, analysing of violation the population rights and their
attempts to protest and appeal against the action of authorized persons. The tax legislation
of population is analyzed in the article, the immediate circumstances of tax collection among
peasants and abuse of taxable contingents, appealing actions of officials as a form of social
and economic protest are studied.
It is established in the researching period of time the constant escalation of amounts
which were produced for payment is presented. Financial mobilizations promoted the forced
trade of rurals on the collective farm markets. The constant and high level of violations in
taxation the various categories of peasants is observed, the evidence of it is the high rates of
satisfaction their complaints.